Baxdrostat an Emerging Drug in Hypertension Therapy - Kayithi Praneetha; B. Samatha; Sayed Shareef; G. Tulja Rani (International Journal of Pharmacy and Analytical Research, 2026)
Hypertension is a major global contributor to cardiovascular morbidity and mortality, and the management of resistant hypertension (RH) remains particularly challenging. Aldosterone synthase inhibitors (ASIs) represent a novel therapeutic class that lowers blood pressure by reducing aldosterone production. Baxdrostat is a selective ASI that inhibits the CYP11B2 enzyme responsible for aldosterone synthesis without interfering with cortisol production, thereby minimizing hormonal adverse effects. Clinical studies have demonstrated that baxdrostat decreases plasma aldosterone levels in a dose-dependent manner while maintaining normal cortisol concentrations. In the Phase 2 BrigHTN trial, baxdrostat significantly reduced both systolic and diastolic blood pressure in patients with RH, with the 2 mg dose providing the most consistent results. However, the HALO trial reported comparable blood pressure reductions in placebo-treated patients, potentially due to improved adherence to background antihypertensive therapy. Overall, baxdrostat has shown a favorable safety profile, with predominantly mild adverse effects and no clinically significant impact on renal function. It is also considered safe for use alongside other medications, including metformin. Ongoing clinical trials are further evaluating its efficacy in patients with chronic kidney disease and primary hyperaldosteronism. Baxdrostat appears to be a promising treatment option for aldosterone-mediated hypertension, particularly in patients who do not respond adequately to conventional therapies.